2022
DOI: 10.3390/psychiatryint3010008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of External Natural Environment Including Sunshine Exposure on Public Mental Health: A Systematic Review

Abstract: The COVID-19 pandemic has been raging around the world and public health measures such as lockdowns have forced people to go out less often, reducing sunlight exposure time, green space use, and physical activity. It is well known that exercise has a positive impact on mental health, but the impact of external environmental factors such as sunlight exposure and green space use on mental health has not been systematically reviewed. In this review, we categorized the major factors that may affect people’s mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…For example, among older adults, only neighbourhood forest exposure seemed to positively affect amygdala integrity, but not urban green or blue spaces (145). The presence of green space in the living environment was associated with reduced risk of depression and anxiety in cross-sectional studies (146), however, non-consistently, and similar associations were not supported by longitudinal studies (97,147). These discrepancies possibly arose due to methodological shortcomings, such as an inability to assess whether participants spent time in those environments, and the mediating effects of air and noise pollution or exercise uptake.…”
Section: Natural Spacementioning
confidence: 98%
See 1 more Smart Citation
“…For example, among older adults, only neighbourhood forest exposure seemed to positively affect amygdala integrity, but not urban green or blue spaces (145). The presence of green space in the living environment was associated with reduced risk of depression and anxiety in cross-sectional studies (146), however, non-consistently, and similar associations were not supported by longitudinal studies (97,147). These discrepancies possibly arose due to methodological shortcomings, such as an inability to assess whether participants spent time in those environments, and the mediating effects of air and noise pollution or exercise uptake.…”
Section: Natural Spacementioning
confidence: 98%
“…Regarding precipitation patterns, limited evidence suggests a possible positive link with mental illness (197)(198)(199). Studies have reported a negative association between sunlight exposure and risk of depression and anxiety (146), while cloudiness and decreased sunshine duration were linked to increased suicide rates (200). Furthermore, seasonal changes directly affect the duration of daylight.…”
Section: Weather Patterns and Climate Changementioning
confidence: 99%
“…In 2021, solar power generated 12.47TWh of electricity, three times the total of 2014 and representing around 4% of all electricity generation. In addition to energy supply, sunshine has other positive societal benefits in the UK such as the promotion of exercise, well-being and improved mental health (Taniguchi et al, 2022), a boost for domestic tourism (Taylor and Ortiz, 2001), and even the enhanced productivity of some agriculture (Arnell and Freeman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in the use of non-pharmacological approaches for improving MH ( Manger, 2019 ). Indeed, there is strong evidence showing the MH benefits of interventions that promote healthy lifestyle behaviors such as exercise ( Josefsson et al, 2014 ; Keating et al, 2018 ), healthy eating ( Jacka et al, 2017 ; Owen and Corfe, 2017 ; Firth et al, 2020 ); sleep ( Freeman et al, 2020 ; Scott et al, 2021 ), and exposure to nature ( Taniguchi et al, 2022 ). In addition, positive psychology practices have been shown to improve MH ( Seligman and Csikszentmihalyi, 2014 ; Carr et al, 2021 ), including expressing gratitude ( Wong et al, 2018 ; Waters et al, 2022 ); identifying and using one’s signature strengths ( Macfarlane, 2019 ); and engaging in service activities ( Walsh, 2011 ).…”
Section: Introductionmentioning
confidence: 99%